Decision Support System to Determine Students Recipient of Smart Indonesia Card (KIP) at Madrasah Aliyah Darul Qalam - Zuryanto Zuryanto; Yupianti Yupianti; Eko Suryana (Jurnal Media Computer Science, 2022)
Smart Indonesia Card (KIP) is the provision of cash assistance for education from Elementary School to Senior High School to all school-age children. The difficulty of ranking in determining students who are eligible to be recommended by KIP recipients is a challenge for Madrasah Aliyah Darul Qalam, where the criteria for the selection process are parents' income, number of dependents, report cards, parental status and housing ownership conditions. To simplify the process, a system is needed to solve the problem using Simple Additive Weighting which is used to rank students with the same characteristics which can then be used as consideration in making policies. The results of the application of the Simple Additive Weighting method can be used by Madrasah Aliyah Darul Qalam in determining the recommendations for KIP recipients based on the ranking results according to the number of students.